English Pronunciation Errors by the Seventh Grade Madurese Students - Nurul Istiana (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2018)
English pronunciation is still a crucial problem among many students of the seventh grade in Junior High School Kamal, Madura. They mostly mispronounce words. The problem is, the students do not realize that they make some pronunciation errors when speaking or reading aloud in English. This usually happens because not all teachers pay much attention to their students’ pronunciation. They just teach the vocabulary found in the text or utterances from the materials and give the examples of how to read them but do not follow up the students’ pronunciation. Being curious with the frequent mispronunciations produced by the seventh grade students, the researcher investigated the problem in her class. The qualitative study employed a single – case study design. To collect the data, a set of pronunciation test were administered. The test consisted three parts: words, phrases and sentences. The findings show that the students produced errors on vowels, consonants and diphthongs